Smart Society in Practice - Case Studies: Austria And Poland - GRZYMAŁA Zbigniew (Communications of International Proceedings, 2022)
The article is the result of a study conducted at the Warsaw School of Economics by a team consisting of Dr. Agnieszka Wójcik-Czerniawska, Krzysztof Witos, MA and the author of this article. The scientific aim of the article was to present practical, in the opinion of the authors, examples of smart society at the level of creating wise economic communities in order to disseminate this idea, among others in Poland and potentially as a result of further studies in other countries. One such example is the creation of an energy-self-sufficient region in Austria in Güssing , which was visited by the author in October 2021. This example was then popularized in Poland in the Kujawsko-Pomorskie voivodeship the instrument of Local Economic Organization (LOG). The research method, apart from the literature review, consisted in conducting an interview with representatives of this region: the mayor of this city and a representative of the Energy Center. During the 4-day visit, the region was explored and information was obtained on how the community of residents and local business were involved in the energy self-sufficiency project. In turn, the assumptions of the instrument which is the Local Economic Organization were created as a result of a project financed by the National Center for Research and Development in Poland called Regiogmina . This project was carried out in the Kuyavian-Pomeranian Voivodeship. The article consists of 3 parts. The first part introduces the meaning of smart society. The following shows the Austrian case study and the aforementioned instrument from a research project conducted in Poland in the Kuyavian-Pomeranian Voivodeship. This instrument to some extent may contribute to the development of solutions similar to those in Güssing.